Aircraft performance and sizing. - Takahashi, Timothy, 1966- (Aerospace engineering collection., 2016)
This book is a concise practical treatise for the student or experienced professional aircraft designer. This volume comprises key applied subjects for performance based aircraft design: systems engineering principles; aircraft mass properties estimation; the aerodynamic design of transonic wings; aircraft stability and control; takeoff and landing runway performance. This book may serve as a textbook for an undergraduate aircraft design course or as a reference for the classically trained practicing engineer.